TINGKAT KONSUMSI BUAH-BUAHAN, KEBIASAAN KONSUMSI KOPI, DAN STATUS HIPERTENSI PRIA DEWASA DI SENDURO SENDURO LUMAJANG - Wahidiyanti, Galih Syevy; Jaelani, Mohammad; Prihatin, Setyo (Poltekkes Kemenkes Semarang, 2015)
Background: Epidemiological transition in Indonesia causes an increase in degenerative diseases, one of which is hypertension. Hypertension is influenced by various factors including fruit consumption, and coffee consumption. The prevalence of hypertension in Lumajang Regency is 24.4%.Objective: To determine the relationship between the level of fruit consumption, and coffee consumption habits with adult male hypertension status in Senduro Village, Senduro District, Lumajang RegencyMethod: This study included the field of clinical nutrition using a cross sectional design involving 54 adult men aged 18 years. Sampling uses Simple Random Sampling. Data collected is the level of consumption of fruits with the consumption survey method, data on coffee consumption habits with interview methods, and sample blood pressure data with direct measurement methods. The test used is Chi Square with α = 0.05.Results: A total of 48.1% of the sample included in the hypertension category, 83.3% of the consumption level of fruits included in the less category, and 66.7% had the habit of consuming coffee with the frequent category. The fruit consumption level did not have a significant relationship with hypertension status, while coffee consumption habits were associated with hypertension status (p = 0.034; OR = 3.64; CI = 95%; 1,068–12,402).Conclusion: Frequent consumption of coffee has a risk of 3.64 times to experience hypertension. There is a tendency to link the lack of fruit consumption with the incidence of hypertension.